2013
DOI: 10.1002/bit.24786
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic reduction of short‐chain carboxylic acids into their corresponding alcohols with syngas fermentation

Abstract: Short-chain carboxylic acids generated by various mixed- or pure-culture fermentation processes have been considered valuable precursors for production of bioalcohols. While conversion of carboxylic acids into alcohols is routinely performed with catalytic hydrogenation or with strong chemical reducing agents, here, a biological conversion route was explored. The potential of carboxydotrophic bacteria, such as Clostridium ljungdahlii and Clostridium ragsdalei, as biocatalysts for conversion of short-chain carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 33 publications
5
71
0
Order By: Relevance
“…Yet, the reversibility of this and similar alcohol forming enzymatic reactions was exploited by providing external short-chain carboxylic acids and syngas to C. ljungdahlii for the production of alcohols [58].…”
Section: Strain Engineering To Obtain Desired Production Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the reversibility of this and similar alcohol forming enzymatic reactions was exploited by providing external short-chain carboxylic acids and syngas to C. ljungdahlii for the production of alcohols [58].…”
Section: Strain Engineering To Obtain Desired Production Phenotypesmentioning
confidence: 99%
“…Thus, it is extremely important to detail the exact mechanisms of energy conservation, including the stoichiometry of the ATPase reaction, in the metabolic network reconstruction for more realistic phenotype predictions. Another model of the WL pathway in C. ljungdahlii was used to determine the ATP yield per mol CO consumed and the proton translocation per electron transfer of the Rnf complex [58]. Lastly, metabolic modeling has been used to optimize media formulations, for instance, based on energy demands [82].…”
Section: Rational Strain Design and Process Optimization Through A Symentioning
confidence: 99%
“…For estimation of the amount of acetic acid produced by a certain amount of cells, it is helpful to note that the concentration of acetic acid in stage one was always ~100 mM per OD 600 . Knowing that the coefficient for milligram dry weight per Liter per OD 600 [mg DW/(L·OD 600 )] is 242 for C. ljungdahlii ERI-2 [17], one can estimate that 1 g DW of cell mass produced about 0.4 mol, or 24 g acetic acid.…”
Section: −1mentioning
confidence: 99%
“…ljungdahlii ERI-2 (ATCC 55380) was used as a biocatalyst, since it had proven to be a good ethanol producer [17]. Bacteria were always grown anaerobically at 35 °C in medium designed for efficient syngas fermentation [22], which is referred to here as 1× medium.…”
Section: Biocatalyst and Growth Conditionsmentioning
confidence: 99%
“…It was recently reported that mono-cultures of C. ljungdahlii and C. ragsdalei as well as a mixed culture of A. bacchi and C. propionicum were able to convert added acids such as propionic, butyric, and hexanoic acids to their respective alcohols (Liu et al, 2014b;Perez et al, 2013). Additional development and optimization of biological gas conversion processes are expected to result in production of various products besides biofuels at commercial scale in the near future.…”
Section: Commercialization and Future Prospectivementioning
confidence: 99%